Tear cytokine levels are reduced in patients treated with intravitreal injections - Malmin, Agni; Thomseth, Vilde M.; Førland, Per T.; Aass, Hans C.D.; Reppe, Sjur; Olsen, Markus V.T.; Lindtjørn, Birger; Chen, Xiangjun; Haugen, Inga B.K.; Utheim, Tor P.; Forsaa, Vegard A. (The ocular surface, 2024)
To investigate cytokine levels in the tear fluid of patients receiving serial intravitreal injections (IVI) with anti-vascular endothelial growth factor (anti-VEGF) for neovascular age-related macular degeneration (nAMD). Concentrations of six cytokines (IFN-γ, IL-1β, IL-6, IL-8, TNF and VEGF) in tears of patients receiving anti-VEGF in one eye were assayed using multiplex cytometric bead array. The fellow untreated eye served as control. Tear sampling was performed on a single occasion at a minimum of four weeks after IVI. Patients underwent a pre-IVI antisepsis protocol with povidone-iodine. Tear fluid from thirty patients with a mean age of 78.8 years (range 58–90) was assayed. Subjects received a median of 43.5 (range 22–106) IVI in one eye. The median level of IFN-γ was 0.33 (interquartile range (IQR) 0.22–0.52) pg/mg of total protein in injected eyes versus 0.41 (IQR 0.21–1.05) pg/mg in fellow eyes (p = 0.017). For TNF, a median level of 0.12 (IQR 0.08–0.18) pg/mg of total protein was found in injected eyes versus 0.14 (IQR 0.07–0.33) pg/mg of total protein in fellow eyes (p = 0.019). There were no differences between injected and fellow eyes regarding the levels of IL-1β, IL-6, IL-8 and VEGF. Tear fluid in eyes receiving serial IVI with anti-VEGF and preoperative povidone-iodine antisepsis constitutes lower levels of the pro-inflammatory cytokines IFN-γ and TNF compared to fellow eyes. This provides biochemical support of previous findings of reduced signs of inflammation and healthier tear film parameters in patients treated with serial IVI.